DEVELOPMENT OF ASEXUAL STAGES OF SARCOCYSTIS AUCHENIAE IN CELL CULTURE - Uzuriaga S, Milagros (2008)
Cystozoites obtained from macrocysts of Sarcocystis aucheniae, collected from alpaca meat infected with sarcocystiosis, were inoculated onto primary monolayer cultures of alpaca turbinate (AT) and secondary monolayer of bovine kidney (BHK) and monkey kidney (VERO) cells. Sporozoites entered the cells, formed large and small multinucleate schizonts, and produced large numbers of cystozoites of perinuclear position. Continuous cultivation from the original cystozoite inoculum was maintained for more than 150 days by inoculating cystozoites onto new cultures of AT, BHK and VERO cells. During this time, the capacity to produce both types of schizonts was preserved. The reproduction of cystozoites of S. aucheniae in tissue culture was confirmed using the Giemsa stain and the fluorescence microscopy and immunoperoxidase test, both of them, using antibodies anti S. aucheniae produced in rabbit.